2021
DOI: 10.3390/ma14041013
|View full text |Cite
|
Sign up to set email alerts
|

Silicon Oxycarbide and Silicon Oxycarbonitride Materials under Concentrated Solar Radiation

Abstract: The potential application of silicon oxycarbonitride (SiOCN), silicon oxycarbide (SiOC) and silicon oxycarbide–SiC (SiOC–SiC) for photothermal devices such as volumetric solar absorbers has been studied evaluating the response to thermal shock from a Fresnel lens. The accelerated ageing test comprises fast heating (32 °C min−1) and cooling rates (27 °C min−1) from 100 to 1000 °C and dwelling times of 10 min. Porous materials (SiOCNp and SiOCp) failed the thermal shock tests; they were massively degraded by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The failure of porous materials due to very aggressive thermal ageing conditions has been reported in Reference [ 37 ]. In that work, it was concluded that the lack of formation of a protective oxide layer during ageing appeared to allow the fluxes to readily diffuse, due to the highly porous microstructure and the severe conditions of the thermal shock test.…”
Section: Discussionmentioning
confidence: 99%
“…The failure of porous materials due to very aggressive thermal ageing conditions has been reported in Reference [ 37 ]. In that work, it was concluded that the lack of formation of a protective oxide layer during ageing appeared to allow the fluxes to readily diffuse, due to the highly porous microstructure and the severe conditions of the thermal shock test.…”
Section: Discussionmentioning
confidence: 99%